CLINICAL FEATURES, DIAGNOSIS AND TREATMENT OF COVID-19 - Ali, J; Ali, Q; Hafeez, MM; Malik, A (Biological and Clinical Sciences Research Journal, 2020)
The COVID-19 has affected worldwide population at every level from advance to under developed countries and also majorly affected clinical microbiology labs. This critique covers current issues furthermore, challenges for the research facility determination of diseases brought about by extreme intense respiratory disorder coronavirus 2 (SARS-CoV-2). In the pre analytical stage, gathering the best possible respiratory diseases information at the time from the privilege has become fundamental for a brief and exact basic finding of COVID-19. Appropriate measures are required to protect lab staffs, performing the test outcomes for COVID-19. In the investigative stage, constant converse translation PCR (RT-PCR) tests remain the basic trial of decision for the etiologic determination of SARS-CoV-2 contamination while counteracting agent-based procedures are being presented as supplemental tests. In the post-analytical stage, testing results ought to be cautiously deciphered utilizing both basic and serological findings. At long last, arbitrary access, testing kits accessible for the purpose of care with versatile limits are encouraging the fast and exact finding and observing of SARS-CoV-2 contaminations and extraordinarily aid the control of this episode.